Differences in Corpse Stiffness (Rigor Mortis) of Organophosphate-Induced and Ordinary (Decerebrated) Dead Wistar Rats : A Randomized Experimental Study - Nugroho, Novianto Adi; Zahrawan, Arzaq Fikrian; Wujoso, Hari; Atmoko, Wahyu Dwi (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Corpse Stiffness (rigor mortis) is a secondary sign of death that can be used to estimate the time and cause of death. Organophosphates are the most toxic pesticides and often cause poisoning until death in humans. This study aims to determine the differences in corpse stiffness (rigor mortis) due to organophosphate poisoning and ordinary death (decerebration) using Wistar rats. The parameters of corpse stiffness (rigor mortis) used include 4 aspects: Corpse Stiffness Appearance, Perfect Formation of Corpse Stiffness, Persistent Corpse Stiffness, and Relaxation of Corpse Stiffness. Data were processed with univariate analysis and then tested with the Independent Sample T-test. There was a significant difference (p<0.05) in the duration of the appearance, perfect formation, persistent and relaxation of corpse stiffness between the control group and the treatment group. Meanwhile, there was no significant difference (p>0.05) in persistent corpse stiffness duration between the control and treatment groups, although there was a slight difference in the mean. Between ordinary and died rats due to organophosphate induction, there was a significant difference in the duration of appearance, perfect formation, and relaxation of corpse stiffness. However, there was no significant difference in the duration of persistent stiffness. Keywords: Organophosphates; Poisoning; Corpse Stiffness; Rigor Mortis